Optimizing Customer Loyalty Through The Information System Customer Approach at Harapan Hospitals - Angelia Dwi Ceissa; Gamayanto, Indra; Wibowo, Sasono (Politeknik Negeri Batam, 2025)
This research aims to optimize hospitals customer loyalty through a Customer Relationship Management (CRM) approach. In the increasingly competitive healthcare industry, customer satisfaction is key to retaining and attracting new customers. SERVQUAL is one of the methods we use in this study so that by implementing CRM, hospitals can understand patient needs, improve service quality, and build long-term relationships. This study uses a quantitative approach with a survey method of 106 respondents who are hospital customers. The results of the analysis show that the implementation of CRM has a significant effect on patient satisfaction and loyalty. Although the overall satisfaction rate reached 84.9%, several aspects needed to be improved, such as the waiting time of doctors and the speed of the registration process. Recommendations to improve the effectiveness of CRM in hospitals include the development of digital systems and staff training.